Heretics! : The Wondrous (and Dangerous) Beginnings of Modern Philosophy - Nadler, Steven M., 1958- (Book collections on Project MUSE., 2017)
"This entertaining and enlightening graphic narrative tells the exciting story of the seventeenth-century thinkers who challenged authority--sometimes risking excommunication, prison, and even death--to lay the foundations of modern philosophy and science and help usher in a new world ... Heretics! tells the story of their ideas, lives, and times in a vivid new way. Crisscrossing Europe as it follows them in their travels and exiles, the narrative describes their meetings and clashes with each other--as well as their confrontations with religious and royal authority. It recounts key moments in the history of modern philosophy, including the burning of Giordano Bruno for heresy, Galileo's house arrest for defending Copernicanism, Descartes's proclaiming cogito ergo sum, Hobbes's vision of the "nasty and brutish" state of nature, and Spinoza's shocking Theological-Political Treatise."--Publisher's description.